CCm performance in Arctic and Antarctic seaweeds in a warming and acidifying marine environment - Íñiguez Moreno, Concepción; Heinrich, Sandra; López-Gordillo, Francisco Javier (My University, 2016)
Ocean acidification and warming are affecting with special intensity the polar coastal ecosystems. The Arctic kelps Saccharina latissima and Laminaria solidungula from Kongsfjorden (Svalbard) were cultured at 4 and 9 ºC in combination with current (390 ppm, CC) and increased (1200 ppm, HC) levels of atmospheric CO2. The Antarctic endemic Desmarestia anceps and D. menziesii were cultured at 2 and 7 ºC, and also at CC and HC.For all these species ∂13C values suggested an absence of deactivation of carbon concentrating mechanisms at increased CO2 levels. The lack of inhibition of CCM at high CO2 shown by ∂13C values seems to be a common pattern in polar species, but it is not related to responses in photosynthesis and growth. Growth of both Arctic species were largely unaffected by increased CO2 conditions, regardless the temperature. In contrast, the Antarctic species were favored by high CO2, specially at the highest temperature. External carbonic anhydrase (eCA) was responsible for about 50% to 80% of the photosynthetic O2 evolution in all the species, according to inhibition assays using DBS. CO2 promoted a decrease in eCA contribution to O2 evolution in the Antarctic species but not in the Arctic ones. The addition of EZ did not promote further inhibition in any species, indicating a low relevance of internal CA, although a concomitant inhibition of eCA may mask this contribution if no other mechanism of active transport was operating. Our latest results of the gene expression of D. anceps reveal that there is a low response to CO2. The relevance of this resilience to CO2 in polar environments will be discussed.
Presentación oral al congreso
Keywords: Fotosíntesis; Carbon concentrating mechanisms; Photosynthesis; Seaweeds; Polar